2013
DOI: 10.1001/jama.2013.4001
|View full text |Cite
|
Sign up to set email alerts
|

Risks of In Utero Exposure to Valproate

Abstract: Antiepileptic medications are among the most commonly prescribed teratogenic drugs among women of childbearing potential. However, determining the exact number of women of childbearing age exposed to antiepileptic medications is difficult. One estimate, based on data from the National Ambulatory Medical Care Survey and the National Hospital Ambulatory Medical Care Survey, suggests that from 2005-2007, there were 7 900 000 annual prescriptions for antiepileptic medications among girls and women aged 15 to 44 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 14 publications
1
27
0
3
Order By: Relevance
“…We hypothesize that one of the major reasons for the alarming rise in autism and autism spectrum disorder is the rise in use of fragrances 2 . It should be noted that autism used to be a relatively rare diseases at the turn of the 20th century [2][3][4][5][6][22][23][24] , but it has now been found that 1 out 88 children is suffering from ASD; again, this may be an underestimate. Since a neonate's brain is still developing after birth, we should expect a rise in other neurological but related conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that one of the major reasons for the alarming rise in autism and autism spectrum disorder is the rise in use of fragrances 2 . It should be noted that autism used to be a relatively rare diseases at the turn of the 20th century [2][3][4][5][6][22][23][24] , but it has now been found that 1 out 88 children is suffering from ASD; again, this may be an underestimate. Since a neonate's brain is still developing after birth, we should expect a rise in other neurological but related conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since a neonate's brain is still developing after birth, we should expect a rise in other neurological but related conditions (e.g. attention de icit hyperactive disorder [ADHD], regressive autism; for example, a child is born normal but begins to show signs of autism after 18 months or later) [21][22][23][24] . ASD is a developmental condition characterized by de icits in social interaction, verbal and nonverbal communication and obsessive/stereotyped patterns of behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Valproic acid (aka 2-propylpentanoic acid, valproate, or VPA), used both to treat epilepsy and as a mood stabilizer in those with bipolar disorder (Roullet, Lai, & Foster, 2013), is a known teratogen, with multiple pregnancy registries confirming an increased risk of major congenital malformations and correlations to reduced cognitive abilities following fetal exposure (Meador & Loring, 2013 and childhood autism (absolute risk, 2.50%; adjusted hazard ratio, 5.2 [95% CI, 2.7-10.0]) among the 508 children exposed to VPA (Christensen et al, 2013). Given the connection between ASD and epilepsy (reported in approximately 1/3 of autism cases) (Muhle et al, 2004;Tuchman, Cuccaro, & Alessandri, 2010), it is noteworthy that the increased risk remained significant after adjusting for parental psychiatric disease and epilepsy (Christensen et al, 2013;Meador & Loring, 2013).…”
Section: Valproic Acidmentioning
confidence: 99%
“…Given the connection between ASD and epilepsy (reported in approximately 1/3 of autism cases) (Muhle et al, 2004;Tuchman, Cuccaro, & Alessandri, 2010), it is noteworthy that the increased risk remained significant after adjusting for parental psychiatric disease and epilepsy (Christensen et al, 2013;Meador & Loring, 2013).…”
Section: Valproic Acidmentioning
confidence: 99%
See 1 more Smart Citation